Enrichment of Anaerobic Syngas-Converting Communities and Isolation of a Novel Carboxydotrophic Acetobacterium wieringae Strain JM - Arantes, Ana L.; Moreira, João P. C.; Diender, Martijn; Parshina, Sofiya N.; Stams, Alfons J. M.; Alves, M. Madalena; Alves, Joana I.; Sousa, Diana Z. (Frontiers in Microbiology, 2020)
Syngas is a substrate for the anaerobic bioproduction of fuels and valuable chemicals. In this study, anaerobic sludge was used for microbial enrichments with synthetic syngas and acetate as main substrates. The objectives of this study were to identify microbial networks (in enrichment cultures) for the conversion of syngas to added-value products, and to isolate robust, non-fastidious carboxydotrophs. Enrichment cultures produced methane and propionate, this last one an unusual product from syngas fermentation. A bacterium closely related to Acetobacterium wieringae was identified as most prevalent (87 % relative abundance) in the enrichments. Methanospirillum sp. and propionate-producing bacteria clustering within the genera Anaerotignum and Pelobacter were also found. Further on, strain JM, was isolated and was found to be 99 % identical (16S rRNA gene) to A. wieringae DSM 1911T. Digital DNA-DNA hybridization (dDDH) value between the genomes of strain JM and A. wieringae was 77.1 %, indicating that strain JM is a new strain of A. wieringae. Strain JM can grow on carbon monoxide (100 % CO, total pressure 170 kPa) without yeast extract or formate, producing mainly acetate. Remarkably, conversion of CO by strain JM showed shorter lag phase than in cultures of A. wieringae DSM 1911T, and about 4 times higher amount of CO was consumed in 7 days. Genome analysis suggests that strain JM uses the Wood-Ljungdahl pathway for the conversion of one carbon compounds (CO, formate, CO2/H2). Genes encoding bifurcational enzyme complexes with similarity to the bifurcational formate dehydrogenase (Fdh) of Clostridium autoethanogenum are present, and possibly relate to the higher tolerance to CO of strain JM compared to other Acetobacterium species. A. wieringae DSM 1911T grew on CO in medium containing 1 mM formate.